43.7k views
0 votes
15 POINTS. PLEASE HELP.

Simplify the expression. (This is a fractions, so "over" is the fraction bar.)
1. 5t ^ -1 over (10t²) (3t^0)

Simplify the expression. (This is a fraction, so "over" is the fraction bar.
2. (2a) (6a²) over 4a³

User Zimex
by
7.7k points

1 Answer

4 votes

1). 5 t⁻¹ / [ (10t²) (3t⁰) ]

t⁻¹ means 1/t and t⁰ is ' 1 ', so the expression becomes

5 / [ t (10t²) (3) ] =

5 / [ 3t (10t²) ] =

5 / 30t³ =

1 / 6 t³ or (1/6) t⁻³


2). (2a) (6a²) / 4a³

Clear the parentheses in the numerator: 2a 6a² = 12a³

So the fraction becomes 12a³ / 4a³

Divide top and bottom by a³ : 12 / 4 = just 3 .


User HyperTrashPanda
by
7.5k points